KARAKTERISASI SPEKTRUM UNSUR Cu UNTUK MENGHITUNG INTENSITAS EMISI ATOM FUNGSI WAKTU TUNDA DENGAN MENGGUNAKAN METODE LASER INDUCED BREAKDOWN SPECTROSCOPY (LIBS) - Efrilinda Diah, Wulansari; Suyanto, Hery; Artawan, I Nengah (BULETIN FISIKA; Vol 14 No 2 (2013): BULETIN FISIKA, 2013)
Laser-Induced Breakdown Spectroscopy (LIBS) is a spectroscopic method is highly reliable for atomic spectrochemical analysis both qualitatively and quantitatively. To achieve this, be aware of the detection parameters, one of which is a function of the atom emission intensity of detection delay time. In this study, plasma is generated by focusing the Nd-YAG laser (1064 nm, 7 ns) on the surface of solid Cu sample with 99.99% purity level at 1 atm pressure air environment. Plasma emission spectrometer was arrested by elements of Cu + HR 2500 with specifications: (wavelength range 200-870 nm, resolution 0.1 nm (FWHM), 7 detector CCDs with a combined 14.336 pixels) with variation detection delay time 0, 0.5, 1, 1.5, and 2 microseconds after the plasma formation and the energy varies the 60-160mJ. The data showed that the value of the Cu atom emission intensity 521.8 nm of the most highly visible on detection delay time decreased to 0.5 microseconds and detection delay time 2 microseconds. Based on these data it can be concluded that the characterization of the elements Cu to calculate the intensity was in the range of 100-140 mJ laser energy and time delay detection of 0.5 microseconds.